Peran Yoga Dalam Meningkatkan Kesehatan Mental, Fisik Dan Kesadaran Spritual Bagi Siswa - Purna Wijaya, I Gede; Suwadnyana, I Wayan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
Health is an optimal physical, mental, and social state, not simply the absence of disease. Implementing wellness involves a healthy lifestyle, health monitoring, good diet, exercise, stress management, and medical care when it is needed. Considering the importance of students' mental and physical health, schools and families can work together to ensure students have optimal health to support students' education. Seeing the rapid progress of technology and the world of education, it cannot be denied that many students are stressed due to cognitive load and so on. The academic environment is a significant source of stress for students which impacts their physical and mental health. This research was prepared using a qualitative approach which displays data processing from observations, interviews, literature, notes or other documents in the form of descriptions using words and accompanied by pictures and not in the form of numbers. yoga practice process at Harapan Nusantara Middle School, Denpasar, guided by a Hindu teacher. Yoha training has a positive impact on individual students' ability to carry out yoga, which will help them to improve mental well-being, help manage stress, increase their concentration in studying and be able to overcome the problem of insomnia faced by today's children. The role of yoga for class VII students at SMP Harapan Nusantara who are aged 12-14 years is very beneficial. By involving students in yoga practices, students here can develop emotionally and physically which is beneficial during the growth period. Currently, without realizing it, all sports activities have a positive correlation with the health of students.